2017
DOI: 10.1080/19393210.2017.1397061
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol in wheat, maize, wheat flour and pasta: surveys in Hungary in 2008–2015

Abstract: Among Fusarium mycotoxins, deoxynivalenol (DON) is the most common contaminant in case of cereals and cereal-based foods in Hungary. In this study, Hungarian wheat (n = 305), maize (n = 108), wheat flour (n = 179) and pasta (n = 226) samples were analysed (N = 818). The samples were collected during 2008-2015 in Hungary. Applied methods of analysis were enzyme-linked immunosorbent assay and liquid-chromatography coupled with a mass spectrometer. Results were compared and evaluated with Hungarian weather data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…The cyclonic front also affected southeast Europe (Serbia, Romania and Bulgaria), with heavy precipitation and floods ( Figure 1 and Figure 3 ) [ 21 , 29 , 30 , 31 , 32 , 33 , 34 ]. The cyclone affected several regions of the European continent, but deoxynivalenol contamination was reported only in durum wheat in northern Italy, wheat, maize and cereals in the Czech Republic, maize in Switzerland, wheat in Hungary, winter wheat and triticale in northwestern Romania, and animal feed across Europe ( Table 1 , Tables S.2.1, S.2.4 and S.3.9 ; Figure 1 , Figure 3 , Figure 4 , Figures S.1.2, S.2.1 and S.4 ) [ 71 , 74 , 77 , 79 , 80 , 83 , 84 , 85 ]. As in the previous year, the 2013 spring, with extreme precipitation and floods, was followed by summer with heat waves and severe drought (Figure S.1.3) [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyclonic front also affected southeast Europe (Serbia, Romania and Bulgaria), with heavy precipitation and floods ( Figure 1 and Figure 3 ) [ 21 , 29 , 30 , 31 , 32 , 33 , 34 ]. The cyclone affected several regions of the European continent, but deoxynivalenol contamination was reported only in durum wheat in northern Italy, wheat, maize and cereals in the Czech Republic, maize in Switzerland, wheat in Hungary, winter wheat and triticale in northwestern Romania, and animal feed across Europe ( Table 1 , Tables S.2.1, S.2.4 and S.3.9 ; Figure 1 , Figure 3 , Figure 4 , Figures S.1.2, S.2.1 and S.4 ) [ 71 , 74 , 77 , 79 , 80 , 83 , 84 , 85 ]. As in the previous year, the 2013 spring, with extreme precipitation and floods, was followed by summer with heat waves and severe drought (Figure S.1.3) [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other European countries, including Italy, Switzerland, the Czech Republic, Slovakia, Hungary, Poland, Lithuania, Croatia, Bosnia and Herzegovina, Albania and Serbia, reported contamination with deoxynivalenol and other mycotoxins in maize, winter wheat, durum wheat, barley, soybean and spelt especially in extremely rainy 2014. Romania reported deoxynivalenol in winter wheat, durum wheat and rye crops [ 12 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. The European and non-European countries that registered the deoxynivalenol-maize outbreak requested a derogation from the maximum allowed limit and received approval from the European Commission [ 6 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most lately, Xu et al ( 2018 ) from North China Plain have detected as high as 95.7% of maize germ contamination with DON and measured average attendance of DON in processed products of maize germs as 163.7–1175.2 μg/kg. In Hungary, Tima et al ( 2018 ) have surveyed the occurrence of DON in maize, wheat and its by-products during the period 2008–2015 and noticed overall mean of 2,159 ± 2,818 μg/kg, which was annoyingly much higher than maximum allowed limit. Besides, Mallmann et al ( 2017 ) have summarized the occurrence of DON and ZEA in barley and wheat grains of Southern Brazil during the middle of 2008–2015 and noticed 67% of DON and 41% of ZEA contamination.…”
Section: Introductionmentioning
confidence: 98%
“…Young et al [8] found that grain processed into pet food still contained DON. Therefore, DON pollution poses a great threat to human and livestock health and has attracted the attention of countries around the world [9]. At present, pollution poses a great threat to human and livestock health and has attracted the attention of countries around the world [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, DON pollution poses a great threat to human and livestock health and has attracted the attention of countries around the world [9]. At present, pollution poses a great threat to human and livestock health and has attracted the attention of countries around the world [9]. At present, at least 100 countries have mandatory limits on DON levels in food and feed.…”
Section: Introductionmentioning
confidence: 99%